Near-field microwave tomography - Gaikovich, K. P.; Gaikovich, P. K.; Maksimovitch, Ye. S.; Badeev, V. A.; Mikhnev, V. A. (Видавництво Національного університету "Львівська політехніка", 2009)
A method of the near-field scanning tomography is developed for the microwave diagnostics of the 3D subsurface structure of permittivity. This method uses data of 2D scanning over lateral co-ordinates above the ground surface with the dipole emitterreceiver system. Measurements at several wavelengths provide the necessary depth sensitivity. The approach to the near-field inverse scattering problem based on the plane wave decomposition of proper Green functions is in use here with taking into account transfer functions of antennas designed for the microwave subsurface sounding. Results are presented for the tomography of 3D permittivity distribution originated by the ice sample buried in the sand.
Keywords: dipole antennas; microwave subsurface sounding; near-field scanning tomography; permittivity